Benzothiadiazole versus Thiazolobenzotriazole: A Structural Study of Electron Acceptors in Solution‐Processable Organic Semiconductors. Issue 22 (30th September 2022) - Watanabe, Nanami; He, Waner; Nozaki, Naoya; Matsumoto, Hidetoshi; Michinobu, Tsuyoshi
Abstract: Despite the rapid progress of organic electronics, developing high‐performance n‐type organic semiconductors is still challenging. Donor‐acceptor (D‐A) type conjugated structures have been an effective molecular design strategy to achieve chemically‐stable semiconductors and the appropriate choice of the acceptor units determines the electronic properties and device performances. We have now synthesized two types of A1 ‐D‐A2 ‐D‐A1 type conjugated molecules, namely, NDI‐BTT‐NDI and NDI‐TBZT‐NDI, with different central acceptor units. In order to investigate the effects of the central acceptor units on the charge‐transporting properties, organic field‐effect transistors (OFETs) were fabricated. NDI‐TBZT‐NDI had shallower HOMO and deeper LUMO levels than NDI‐BTT‐NDI. Hence, the facilitated charge injection resulted in ambipolar transistor performances with the optimized hole and electron mobilities of 0.00134 and 0.151 cm 2  V −1  s −1, respectively. In contrast, NDI‐BTT‐NDI displayed only an n‐channel OFET performance with the electron mobility of 0.0288 cm 2  V −1  s −1 . In addition, the device based on NDI‐TBZT‐NDI showed a superior air stability to that based on NDI‐BTT‐NDI. The difference in these OFET performances was reasonably explained by the contact resistance and film morphology. Overall, this study demonstrated that the TBZ acceptor is a promising building block to create n‐type organic semiconductors. Abstract : Acceptor structures of benzothiadiazole (BT) and thiazolobenzotriazole (TBZ) are compared for use in organic field‐effect transistors. The TBZ‐based semiconductor showed one order of magnitude higher electron mobility than the BT‐based semiconductor. This is due to its charge injection efficiency and film forming capabilities.